On the need for sustainable tourism consumption. (March 2021) - Sharpley, Richard
Sustainable tourism has remained the dominant tourism development paradigm within both academic and policy circles for more than three decades. However, little if any progress has been made towards implementing sustainable tourism in practice. Reflecting on this failure to achieve a more sustainable tourism sector, manifested not least in its increasing contribution to climate change, this paper argues that the problem lies in the continuing adherence to the economic growth model that underpins (sustainable) development policies in general and tourism development in particular. Highlighting the unsustainability of unabated growth, the paper goes on to suggest that the solution lies in the adoption of sustainable (reduced) levels of consumption. Yet, based on a recent exploratory study, voluntary limiting the consumption of tourism, even amongst the allegedly environmentally aware post-millennial generation, is an unlikely scenario. Hence, the path to sustainable tourism production and consumption lies only in effective regulation.